Legalization of Bride measure to detect talented children in kindergarten in Damascus governorate - Daowd, Farah Nizar (Journal of Educational and Psychological Sciences, 2021)
This research aims to identify the methods of detection and diagnosis of gifted children in pre-school stage, where a modified Syrian image was developed on the BRIDE scale for the detection of gifted in pre-school stage, with indications of validity, stability, and effectiveness of the Syrian environment paragraphs.The process of preparing the scale included a number of stages and procedures, represented in preparing an image of the scale and reviewing it by a number of arbitrators in the Department of Special Education and Educational and Psychological Measurement and Evaluation, and then applying that image to a sample of 100 boys and girls representing a number of kindergartens in Damascus governorate. Then, the data resulting from the application process was analyzed, and indications were reached about the discriminatory honesty, as it was found that there is a difference in favor of the first group (higher) whose average is greater, and this indicates that the scale is characterized by a discriminatory ability in favor of the higher group in the total score of the scale, The validity of the inter-correlations was studied and it was found that most of the correlations of the items of the scale are significant at the significance level (0.01) and the significance level (0.05), and the spoken honesty was studied with the significance of another criterion, which is the Stanford test, which shows the fifth standardized picture on the Syrian environment and fig. The values ​​of the correlation of the verbal knowledge test with the domains of the Pride scale and its total score ranged between (0.819-0.387), while we notice the correlation values ​​with the matrix test (0.836-0.318). As for the indicators of scale stability, it was calculated in two ways, namely, the repeat method (0.915) and the half-segment method (0.892).
Keywords: talent; kindergarten; pride; legalization